2016
DOI: 10.18632/oncotarget.8433
|View full text |Cite
|
Sign up to set email alerts
|

REST reduction is essential for hypoxia-induced neuroendocrine differentiation of prostate cancer cells by activating autophagy signaling

Abstract: Prostate cancer (PCa) with neuroendocrine differentiation (NED) is tightly associated with hormone refractory PCa (HRPC), an aggressive form of cancer that is nearly impossible to treat. Determining the mechanism of the development of NED may yield novel therapeutic strategies for HRPC. Here, we first demonstrate that repressor element-1 silencing transcription factor (REST), a transcriptional repressor of neuronal genes that has been implicated in androgen-deprivation and IL-6 induced NED, is essential for hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
72
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 67 publications
(109 reference statements)
4
72
0
Order By: Relevance
“…Several laboratories including ours have demonstrated that REST is a novel regulator of human PCa cell NED910111213. The terminally differentiated NE cells are recognized as a potential cause of CRPC and apparent acquisition of stemness properties in advanced CRPC7.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Several laboratories including ours have demonstrated that REST is a novel regulator of human PCa cell NED910111213. The terminally differentiated NE cells are recognized as a potential cause of CRPC and apparent acquisition of stemness properties in advanced CRPC7.…”
Section: Resultsmentioning
confidence: 91%
“…NE-like cell development relies on a network of transcriptional reprogramming that controls the acquisition and maintenance of neuronal features. Recent reports including ours provide evidence showing that repressor element-1 (RE-1) silencing transcription factor (REST) expression is significantly reduced in relapsed PCa tissue912 and reduction of REST is responsible for NED of PCa cells910111213. REST was originally identified as a transcription repressor for neuron-specific genes in neuronal progenitor and non-neuronal cells14.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Our recent reports show that knockdown of REST may induce NED through activation of autophagy1114, a pathway that eukaryotic cells use to degrade long-lived proteins and organelles in response to stress17. However, little is known about the underlying mechanisms for REST-mediated autophagy activation.…”
mentioning
confidence: 99%
“…Prostate cancer cells subjected to hypoxia for 3 or 7 days exhibit features of NED including neurite lengthening and the upregulation of neuronal markers such as ENO2, ÎČ-Tubulin III, CgA and ASH-1 [32–34]. We recently reproduced the hypoxic (1% O 2 for 6 days) induction of ENO2 and CgA in LNCaP cells, but we saw only partial neurite lengthening [17].…”
Section: Resultsmentioning
confidence: 94%